Quality Management of Educators and Education Personnel Based on Performance Improvement and Sustainable Development in the Modern Era - Fadillah, M Kharis (STAI Serdang Lubuk Pakam, 2025)
This study aims to analyze the quality management of educators and educational staff at MAN 3 Malang based on performance improvement and sustainable development in the modern era. The main focus of this study is on the implementation of human resource management functions, including planning, development, and assessment, in order to improve the quality of educators' performance. A qualitative approach was used with a case study method, where data was collected through observation, interviews, and document analysis. The results of the study indicate that MAN 3 Malang places greater emphasis on improving the quality of educators through training, seminars, workshops, and encouragement to pursue formal education, rather than hiring new staff. The assessment function is carried out in a structured manner by a quality assurance team through academic competency tests, which aim to evaluate the effectiveness of teachers' work and serve as a basis for continuous development. These findings indicate that integrated sustainable development strategies and performance evaluation are key to maintaining educational quality. However, limitations in recruitment may pose a challenge in the long term if not balanced with comprehensive human resource planning.